Electrodermal Response to Mirror Exposure in Relation to Subjective Emotional Responses, Emotional Competences and Affectivity in Adolescent Girls With Restrictive Anorexia and Healthy Controls - Knejzlíková, Terézia; Světlák, Miroslav; Malatincová, Tatiana; Roman, Robert; Chládek, Jan; Najmanová, Jana; Theiner, Pavel; Linhartová, Pavla; Kašpárek, Tomáš (Frontiers in Psychology, 2021)
Objective: Body image disturbances and the attendant negative emotions are two of the major clinical symptoms of eating disorders. The objective of the present experimental study was to shed more light on the degree of association or dissociation between the physiological and emotional response to mirror exposure in patients with restrictive mental anorexia, and on the relationships between the physiological response and characteristics connected with emotional processing. Materials and Methods: Thirty adolescent girls with the restrictive type of anorexia and thirty matched healthy controls underwent bilateral measurement of skin conductance (SC) during rest, neutral stimulus exposure, and mirror exposure, and completed a set of measures focused on emotion regulation competencies, affectivity, and eating disorder pathology. Results: Compared to healthy controls, girls with restrictive anorexia rated mirror exposure as a subjectively more distressful experience. Differences in skin conductance response (SCR) were not significant; however, variance in SCR was substantially greater in the group of anorexia patients as compared to healthy controls. The overall skin conductance level (SCL) was lower in anorexia patients. Increase in SCR during mirror exposure, as opposed to exposure to neutral stimuli, was positively related to the tendency to experience negative emotions, interoceptive sensitivity, body dissatisfaction and suppression, but not to other symptoms of eating pathology or emotional awareness. A post-hoc analysis suggested that physiological reactivity might be associated with interoceptive sensitivity to mirror exposure especially in anorectic patients. Conclusion: The study seems to demonstrate some degree of dissociation between psychophysiological reactivity and subjective response to body exposure in patients with restrictive anorexia. Factors affecting differences in psychophysiological responsiveness to body exposure in anorectic patients require further exploration.